تطبيق طريقة مباشرة في تعليم مهارة الكلام بمعهد خادم الحرمين الشريفين أتشيه - Fauzi, Firman Nurul; Aramina, Aramina; Bahruddin, Uril (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Up until today, learning maharah kalam through direct technique has proven to be highly successful. So this study aimed to determine: 1) the application of the direct method in learning maharah kalam, 2) supporting and inhibiting factors in the direct method in learning maharah kalam, and 3) the influence of the direct method on learning maharah kalam. This research used descriptive qualitative research with data collection through interviews and documents analysis. The results showed that (1) the application of the direct method in learning maharah kalam at ma'had khadimul haramain asy-syarifain began with direct material exposure using Arabic, explaining mufradat by mentioning similarities or opponents and re-exposure using Arabic. (2) The supporting and inhibiting factors were divided into two, namely internal from the student or teacher and external from the learning environment. (3) The application of this direct method had a very large effect on increasing students' maharah kalam so that they were able to speak in the Arabic style. To conclude, the application of this direct method is the right solution in learning maharah kalam.